Dostoevsky: Religion, Art, and Nihilism - Cabral, Jimmy Sudario (TEOLITERARIA - Revista de Literaturas e Teologias, 2018)
To interpret Dostoevsky's thinking as a kind of apophatic method means to assume the impossibility of understanding it without first assuming the intrinsic connection between religion and art, which is the basis of his realism. By separating aesthetics from religion in Dostoevsky's works, one runs the risk of falling into the common misunderstanding of a certain criticism which considered that the aesthetic deconstruction experienced by the artist did not reach the fundamental nucleus of the religious thinker. This paper will argue that the apophatic suspension wich offers the religious tone to Dostoevsky's works is the result of a particular aesthetic reconfiguration of religion in the light of nihilism and can be interpreted as a particular interweaving between the aesthetic-religious elements found in Shakespeare and Cervantes, and the core of the apophatic spirituality of Eastern Christianity.